Bioecology of the mango mealybug, Rastrococcus iceryoides green (Hemiptera : Pseudococcidae) and its associated natural enemies in Kenya and Tanzania - Mohammed, S. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2013.